Os trios de avondano em Dresden : uma abordagem interpretativa - Costa, Manoella Coutinho (2017)
The manuscripts of three sonatas in trio attributed to sgnr Avondano are in the Public Library of Dresden under cataloging D-DI. Mus.2661-Q-1, D-DI. Mus.2661-Q-2 and D-DI. Mus.2661-Q-3. Its transcription was developed by Francisco Jaime Cordeiro da Costa at the Laboratory of Musicology and Cultural History of the State University of Amazonas. The intended approach of these compositions is initially an analysis on the condition of the performer and its context in relation to such repertoire, and then, develop an interpretative analysis in which rhetorical elements can be evidenced and added to the variety of topical and styles present in the trios. The objective of this research also includes examining relevant structural aspects and authorship criticism, in order to produce information that collaborates with the interpretation and execution of the trios as the final product of the research. Keywords: Avondano. Sonate. Performance practices. Topics and Musical Rhetoric. Topics. Violin. Musicology